2019
DOI: 10.1038/s42255-019-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased β-cell proliferation before immune cell invasion prevents progression of type 1 diabetes

Abstract: Type 1 diabetes (T1D) is characterized by pancreatic islet infiltration by autoreactive immune cells and a near-total loss of β-cells1. Restoration of insulin-producing β-cells coupled with immunomodulation to suppress the autoimmune attack has emerged as a potential approach to counter T1D2–4. Here we report that enhancing β-cell mass early in life, in two models of female NOD mice, results in immunomodulation of T-cells, reduced islet infiltration and lower β-cell apoptosis, that together protect them from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 51 publications
4
44
0
Order By: Relevance
“…in the population of Tregs. Of interest, the estrogen signalling pathway was robustly upregulated in these cells consistent with previous data demonstrating that ER-alpha binds the FOXP3 gene promoter driving Tregs expansion and anti-inflammatory function [45,139]. As previously stated (see Section 6.1), we and others have highlighted a cross-talk between LRH-1/NR5A2 and ER-alpha that intimately cooperate to activate common target genes suggesting a role of LRH-1/NR5A2 in promoting the expansion of the Tregs population through a potential interaction with the FOXP3 gene promoter [94][95][96].…”
Section: The Anti-diabetic Benefits Of the Bl001/lrh-1/nr5a2 Signallisupporting
confidence: 88%
See 1 more Smart Citation
“…in the population of Tregs. Of interest, the estrogen signalling pathway was robustly upregulated in these cells consistent with previous data demonstrating that ER-alpha binds the FOXP3 gene promoter driving Tregs expansion and anti-inflammatory function [45,139]. As previously stated (see Section 6.1), we and others have highlighted a cross-talk between LRH-1/NR5A2 and ER-alpha that intimately cooperate to activate common target genes suggesting a role of LRH-1/NR5A2 in promoting the expansion of the Tregs population through a potential interaction with the FOXP3 gene promoter [94][95][96].…”
Section: The Anti-diabetic Benefits Of the Bl001/lrh-1/nr5a2 Signallisupporting
confidence: 88%
“…Interestingly, a recent study reported that boosting beta-cell mass through insulin resistance-induced proliferation in NOD mice before the onset of the autoimmune attack delayed the development of hyperglycemia. The latter was conveyed by the preservation of the immunological self-tolerance of islet through an expansion of Tregs [45]. Although the proliferation of beta-cells is detected in mouse models of T1DM and T2DM and can be prompted by various stimuli such a GLP-1, human islet beta-cells are more reluctant to proliferate under stress conditions [46][47][48].…”
Section: Beta-cell Regeneration Therapiesmentioning
confidence: 99%
“…After 48 hours, Intraperitoneal glucose tolerance test, insulin tolerance test, and in vivo glucose-stimulated insulin secretion. Glucose tolerance tests (GTTs) and insulin tolerance tests (ITTs) were performed as previously reported (60)(61)(62). Briefly, for GTT, animals were fasted for 16 hours overnight, and 20% (vol/vol) dextrose was given through an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is noteworthy that islets from these protected mice are less vulnerable but not resistant to autoimmunity when transferred into unprotected recipients and that, conversely, bone marrow transfer from unprotected mice into protected recipients triggers diabetes. Indeed, proliferating beta cells exerted an indirect protective effect by modulating T cell selfreactivity and boosting regulatory T cells [57], an observation that underlines the far-reaching effects of this immune-beta cell crosstalk. Mirroring these mouse studies, two human case reports lend strong arguments for an initiating role of immune cells: (1) twin-to-twin transplantation of a non-diabetic pancreas into a type 1 diabetic recipient led to rapid autoimmune relapse [58]; and (2) conversely, bone marrow transplantation from a HLA-identical type 1 diabetic sibling into a non-diabetic recipient led to the development of type 1 diabetes [59].…”
Section: Autoimmune Vs Beta Cell Disease: Chicken or Egg?mentioning
confidence: 96%
“…Is the initiation of islet autoimmunity triggered by immune cells or by the beta cells themselves? In support of the latter possibility, altering the identity of beta cells by boosting their proliferation protects NOD mice from autoimmune diabetes [57]. However, it is noteworthy that islets from these protected mice are less vulnerable but not resistant to autoimmunity when transferred into unprotected recipients and that, conversely, bone marrow transfer from unprotected mice into protected recipients triggers diabetes.…”
Section: Autoimmune Vs Beta Cell Disease: Chicken or Egg?mentioning
confidence: 99%